2021
DOI: 10.3348/jksr.2020.0213
|View full text |Cite
|
Sign up to set email alerts
|

Shock Thyroid in a Patient with Septic Shock: A Case Report and Literature Review

Abstract: Shock thyroid is a rare manifestation of the CT hypotension complex and can be diagnosed when thyroid and perithyroidal edemas are observed on CT during the onset of shock. Shock thyroid can be a useful CT sign for decompensated shock. This condition is reversible and recovers rapidly with adequate treatment. We present the case of an 84-year-old female with septic shock, exhibiting CT features consistent with a shock thyroid. We also reviewed the clinical and radiological findings reported in the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Thyroid findings are an uncommon, largely unknown part of the CT hypotension complex [ 19 , 21 , 25 , 26 ]. To our knowledge, only eight cases have been reported in the literature [ 77 ]. In their initial description, Brochert et al observed a distinct pattern of heterogeneous hyperenhancement in the thyroid gland, resembling the appearance of a multinodular gland.…”
Section: Ct-updated Hsc Findings As Diagnostic Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations
“…Thyroid findings are an uncommon, largely unknown part of the CT hypotension complex [ 19 , 21 , 25 , 26 ]. To our knowledge, only eight cases have been reported in the literature [ 77 ]. In their initial description, Brochert et al observed a distinct pattern of heterogeneous hyperenhancement in the thyroid gland, resembling the appearance of a multinodular gland.…”
Section: Ct-updated Hsc Findings As Diagnostic Biomarkersmentioning
confidence: 99%
“…The presumed mechanism is that hypoperfusion of the highly vascular thyroid gland may cause cellular edema or death as well as exudation of intracellular fluid. Other proposed explanations include third-spacing of resuscitative fluid and a profound thyroid response, which induces transient thyrotoxicosis and a swollen gland for the maintenance of cardiac output [ 25 , 77 , 78 , 79 ]. These glandular changes are reversible when associated with successful management of hypovolemia and hypotension [ 77 ].…”
Section: Ct-updated Hsc Findings As Diagnostic Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations